Respons Pertumbuhan dan Produksi Bawang Merah (Allium ascalonicum L.) Terhadap Komposisi Pemberian Abu Vulkanik Gunung Sinabung, Arang Sekam Padi dan Kompos Jerami - Lis Amelia Anggun Purba; Yaya Hasanah; Haryati Haryati (Jurnal Agroekoteknologi, 2015)
Volcanic ash had an acidic pH may degrade agricultural lands and the result of shallot production.The composition of giving about the volcanic ash, rice husk charcoal and rice straw compos canhelp the availability of nutrients through the release of organic acids thereby creating a plantingmedium that supports the growth and production of shallot. The objective of the research was todetermine the effect of composition of giving about the volcanic ash, rice husk charcoal and strawcompost on the growth of shallot. The research was done at experimental field of AgriculturalFaculty, University of Sumatera Utara, Medan in July-September 2014. The research usedrandomize block design with seven treathments and three replications. This study used arandomized block design Non Factorial with ten treatments and three replications. Parameterobserved were tillers number, wet weight per sample, wet weight per plot, dry weight per sample,dry weight per plot. The results of research showed that the composition of giving about thevolcanic ash, rice husk charcoal and straw compost influence significantly the parameters of tillersnumber 4 MST. There are no significant different for wet weight per sample, wet weight per plot,dry weight per sample, dry weight per plot.. The composition of giving volcanic ash 5 ton/ha + ricehusk charcoal 5 ton/ha + straw compost 3,75 ton/ha was the the best composition to produce tillersnumber of shallots.Keywords : rice husk charcoal, shallot, straw compost, volcanic ash